Penerapan Teknologi Augmented Reality sebagai Media Pembelajaran Interaktif Tata Surya - Meisye Putri Azizah; Rr. Hajar Puji Sejati (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Learning the solar system through books has been a major choice over time. This learning is considered monotonous because of the limited interaction of students with the delivery of material. The book only presents text and static images of the solar system planets that limit their safety. The research is aimed at building an application as an interactive learning medium in the solar system that utilizes augmented reality technology to overcome restrictions on books. Using the Multimedia Development Life Cycle (MDLC) method as a systematic framework that has six stages, namely concept, design, material collection, assembly, testing, and distribution, The research has successfully built an augmented reality solar system application using Unity 3D on Android devices. The application uses a marker-based tracking method, where there is an image card that will be identified by the camera and then processed to display 3D Solar System planet objects, matter, and voice elements on the smartphone screen. Tested applications using black box testing techniques on application features and image markers show that all systems are running well, so applications can be distributed to Tlacap State SD. Through this built-in Solar System Augmented Reality application, learning becomes more interactive, and students' understanding of the planets of the Solar System can be enhanced.